Resilience and creativity in elementary school children - Jeong J., Kim (2019)
The present study aimed to identify the relationship between creativity and resilience in elementary school children. The study design was correlational descriptive, and the sample used was 320 students distributed in 3rd, 4th, 5th and 6th grades of primary of a national educational institution, with ages between 8 and 13 years. The instruments used were Basic Indicators of Creativity (Sánchez, 1991), and the Inventory of Personal Factors of Resilience created by Salgado (2004), both were elaborated in the Peruvian reality. The results obtained demonstrate the positive and significant relationship between the resilience factors and the creativity indicators in primary school children.